2017
DOI: 10.5489/cuaj.4243
|View full text |Cite
|
Sign up to set email alerts
|

An in-house Composix™-based pubovaginal sling trial for female stress urinary incontinence: Five-year comparative followup to tension-free and transobturator vaginal tapes

Abstract: Introduction: We compared the efficacy of three slings in the longterm treatment of stress urinary incontinence (SUI): tension-free vaginal tape (TVT), vaginal tape-obturator (TVT-O), and an in-house two-layered polypropylene mesh with a submicronic polytetrafluoroethylene (Composix™). Our primary endpoint was the objective measurement of continence (24-hour pad test). Secondarily, we measured the satisfaction and complication rates. Methods: This prospective, non-randomized study included 128 patients with SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Urinal bladder perforation is one of the most common intraoperative complications. Studies have demonstrated this in 0.7-24% of TVT procedures [17,[21][22][23]. Our result is consistent with the one reported by Ford et al [9] (4.5%), who analysed 8,652 TVT procedures.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Urinal bladder perforation is one of the most common intraoperative complications. Studies have demonstrated this in 0.7-24% of TVT procedures [17,[21][22][23]. Our result is consistent with the one reported by Ford et al [9] (4.5%), who analysed 8,652 TVT procedures.…”
Section: Discussionsupporting
confidence: 93%
“…This can be explained by the lower percentage of urinal bladder perforations and fewer voiding difficulties after surgery in this group of patients. In the studies of Ben Zav et al [21] and Luo et al [22], damage to the urinal bladder was only observed during the TVT procedure. In our material, post-operative urine retention occurred twice as many times as among patients who underwent TVT, whereas Ben Zvi et al [21] and Cavkaytar et al [11] observed this kind of complication in an equal percentage among patients operated on using the TOT and TVT procedure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations